Influência da costura na performance de meios filtrantes aplicados em filtro de mangas - Lacerda, Camila Raquel de (2022)
There is a variety of filter bags available in the market for cleaning gases, composed of different materials, of various sizes, with several surface treatments, high efficiency, and different finishes, which enables the application in the most diverse thermal and chemical conditions. When making the filter bags, the filter medium is sewn in a cylindrical shape to be installed in industrial bag filters. Although the sewing area is approximately 4% of the total area of an industrial filter bag, it is necessary a broader investigation of the influence of this region in filtration, because the small holes can be a conduit for the passage of fine particles even after a certain time of use of the filter bags. Therefore, this work aimed to evaluate the filtration performance – regarding the mechanisms of deposition, the cake porosity, the duration of filtration cycles, the differential pressure, the fractional separation efficiency, and particle emission - of two distinct groups of filter media, both containing samples without and with seam, the first group of samples with different aging times and the second with virgin samples sewn with needles of different diameters. In a first step, samples of polyimide (P84) filter bags, virgin, with 10 months of use and with 3 years of use (the latter two were used in an industrial bag filter), and particulate material from a sintering plant (the primary process of dedusting) were used. The samples were submitted to filtration and cleaning cycles in laboratory equipment built based on the VDI 3926 standard, to analyze the pressure drop, the cycle time and to estimate the cake porosity. Particle collection was also performed for diameters in the range from 0.523 to 2.8 μm, on a second filtration test rig containing a particle counter (Aerodynamic Particle Sizer-APS), and in the range from 10 to 300 nm, in a third particle analysis system by differential electric mobility (Scanning Mobility Particle Sizer - SMPS), in order to evaluate the separation efficiency and relate the results to the performance of the particle deposition mechanisms when there is the presence of seam. The results showed that in the seam region the preferential paths for the airflow had effects on the particle deposition mechanisms. The total filtration time was longer for the samples with seam. In a second step, polyester filter media with a polytetrafluoroethylene (PE/PTFE) membrane, sewn with different needle diameters, 90, 100, and 130 µm, and Pural SB® powder, were used. An investigation of the impact of the needle diameter on fractional separation efficiency and particle emissions was conducted, respectively, on MFP 3000 HF (Modular Filter Test System) and VDI 3926-based test rigs (the latter is not the same equipment used in the first group of samples), both belonging to the Karlsruhe Institute of Technology. While the sample without seam showed a particle separation of almost 100%, the increase in needle diameter led to an increase in particle emissions. The sewn samples with needle diameters of 100 and 130 µm did not have the holes completely sealed by the dust even after all steps of the filtration procedure adapted from VDI 3926 standard.